(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
In this paper we utilized mixing of different types of recycled glass such as (neon glass, brown glass, and green glass) that has high percentage of silicon dioxide (SiO2) with different concentrations. Utilization these landfall materials can be considered as keeping on resources. Different waste glasses used as a partial replacement of cement with different concentrations 11%, 13%, and 15% of cement weight for each type, and study the effect of it on the mechanical properties of concrete. After mixing, casting, and curing in water at (20±2)°C for (7, 14, and 28) days, the mechanical properties showed that the compressive strength and flexural showed highest results at 13% from cement weight of neon glass, whereas splitting tensile strength showed the highest value at the same percentage, but from green glass.